An analysis of solar assisted ground source heat pumps in cold climates. (December 2015) - Emmi, Giuseppe; Zarrella, Angelo; De Carli, Michele; Galgaro, Antonio
Highlights: The work focuses on solar assisted ground source heat pump in cold climates. Multi-year simulations of SAGSHP, are carried out in six cold locations. GSHP and SAGSHP are compared. The effect of total borehole length on the heat pump energy efficiency is studied. A dedicated control strategy is used to manage both solar and ground loops. Abstract: Exploiting renewable energy sources for air-conditioning has been extensively investigated over recent years, and many countries have been working to promote the use of renewable energy to decrease energy consumption and CO2 emissions. Electrical heat pumps currently represent the most promising technology to reduce fossil fuel usage. While ground source heat pumps, which use free heat sources, have been taking significant steps forward and despite the fact that their energy performance is better than that of air source heat pumps, their development has been limited by their high initial investment cost. An alternative solution is one that uses solar thermal collectors coupled with a ground source heat pump in a so-called solar assisted ground source heat pump. A ground source heat pump system, used to heat environments located in a cold climate, was investigated in this study. The solar assisted ground source heat pump extracted heat from the ground by means of borehole heat exchangers and it injected excess solar thermal energy into the ground. Building load profiles are usually heating dominated in cold climates, but when common ground source heat pump systems are used only for heating, their performance decreases due to an unbalanced ground load. Solar thermal collectors can help to ensure that systems installed in cold zones perform more efficiently. Computer simulations using a Transient System Simulation (TRNSYS) tool were carried out in six cold locations in order to investigate solar assisted ground source heat pumps. The effect of the borehole length on the energy efficiency of the heat pump was, in particular, analyzed. Finally, a suitable control strategy was implemented to manage both the solar thermal collectors and the borehole heat exchangers.